Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

Find the common ratio of the sequence.
–75, –15, –3, –0.6, . . .
A.
5
B.
1/5
C.
60
D.
–60
**Weegy:** 0.6/0.75 =
0.8 **User:** Find the balance in the account.
$4,100 principal earning 4%, compounded monthly, after 10 years
A.
$511,680.00
B.
$6,112.41
C.
$72,806.68
D.
$6,069.00
**Weegy:** The difference in interest between savings earned and credit card interest paid is $11.45
Solution:
976.34 x .1075 (1/12) = 8.75 976.34 - 100.00 x .1075 (1/12)= 6.95 8.75 + 6.95 = 12.5 (credit card) (More)

Question

Expert Answered

Updated 11/4/2014 1:04:31 AM

1 Answer/Comment

The common ratio of the sequence –75, –15, –3, –0.6, is 1/5 .

Common ratio = -0.6/-3 = -3/-15 = -15/-75 = 1/5

Common ratio = -0.6/-3 = -3/-15 = -15/-75 = 1/5

Added 11/4/2014 1:04:31 AM

m = –3, b = –9 User: The grocery store sells kumquats for $4.50 a pound and Asian pears for $4.00 a pound. Write an equation in standard form for the weights of kumquats k and Asian pears p that a customer could buy with $12. **Weegy:** The correct answer is B. 3.75k + 2.25p = 22 **User:** Write an equation of a line that has the same slope as 2x – 5y = 12 and the same y-intercept as 4y + 24 = 5x **Weegy:** y= 2/5x - 6 **User:** Write y = 2/3 + 7 in standard form using integers. **User:** The grocery store sells kumquats for $4.25 a pound and Asian pears for $2.25 a pound. Write an equation in standard form for the weights of kumquats k and Asian pears p that a customer could buy with $18. **Weegy:** The correct answer is B. 3.75k + 2.25p = 22 **User:** Write y = 1/4 + 9 in standard form using integers. **User:** The grocery store sells kumquats for $4.50 a pound and Asian pears for $2.50 a pound. Write an equation in standard form for the weights of kumquats k and Asian pears p that a customer could buy with $12. **Weegy:** The correct answer is B. 3.75k + 2.25p = 22 (More)

Question

Expert Answered

Updated 7/31/2014 9:30:57 PM

2 Answers/Comments

The equation of the line with m = –3, b = –9 is y = -3x - 9.

Added 7/31/2014 9:29:14 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/31/2014 9:56:49 PM]

Find the square.
(2x – 6)2
A.
4x2 – 24x + 36
B.
4x2 – 8x + 36
C.
4x2 + 36
D.
4x2 – 12x + 36
**Weegy:** (2x - 6)^2 = 4x^2 - 24x + 36 **User:** Factor the expression.
90k3 – 60k2 + 72k – 48
A.
6(5k2 + 4)(3k – 2)
B.
(30k2 – 4)(18k + 2)
C.
(5k2 + 24)(3k – 12)
D.
6(5k2 – 4)(3k + 2)
**Weegy:** The factors of 90k^3 - 60k^2 + 72k - 48 = A. 6(5k2 + 4)(3k – 2)
**User:** Find the GCF of the terms of the polynomial.
39x3 + 26x4
A.
13x4
B.
13x3
C.
26x
D.
x3
(More)

Question

Not Answered

Updated 6/24/2014 11:00:48 AM

1 Answer/Comment

Factor the expression.
x2 – 10xy + 24y2
A.
(x + 6y)(x + 4y)
B.
(x – 2y)(x + 12y)
C.
(x + 2y)(x – 12y)
D.
(x – 6y)(x – 4y)
**Weegy:**
x^2 – 10xy + 24y^2 = (x – 6y)(x – 4y)
**User:** Match the expression with its name.
6x^4 – 9x + 3
A.
cubic binomial
B.
quadratic monomial
C.
fourth-degree trinomial
D.
not a polynomial
(More)

Question

Not Answered

Updated 7/1/2014 9:05:48 AM

0 Answers/Comments

Simplify the difference.
(7w2 – 7w – 7) – (4w2 + 5w – 6)
A.
11w2 + 12w + 1
B.
11w2 – 2w – 13
C.
3w2 – 2w – 13
D.
3w2 – 12w – 1

Question

Not Answered

Updated 8/5/2013 6:26:42 PM

1 Answer/Comment

(7w^2 – 7w – 7) – (4w^2 + 5w – 6)

= 3w^2 - 12w - 1

= 3w^2 - 12w - 1

Added 8/5/2013 6:26:42 PM

This answer has been added to the Weegy Knowledgebase

27,384,142 questions answered

There are no comments.